2001
DOI: 10.2337/diacare.24.7.1156
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Fasting Plasma Glucose Values and Other Variables to 2-h Postload Plasma Glucose in Japanese Subjects

Abstract: OBJECTIVE -To investigate the relationship between fasting plasma glucose (FPG) values and other variables (e.g., age, sex, and BMI) to 2-h post-75-g oral glucose load glycemia (PG) in Japanese subjects.RESEARCH DESIGN AND METHODS -Subjects included 13,694 Japanese subjects between 20 and 83 years of age (10,677 men and 3,017 women) who were undergoing a 75-g oral glucose tolerance test (OGTT) during a health screening performed at our hospital. The influences of age for 2-h PG at a fixed fasting plasma glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…These results confirm our hypothesis indicating that in general the measurement of 2‐hour OGTT glucose values cannot be replaced by determining FPG, and vice versa. They also support the results of a study conducted in a North Indian population but contrast with those from adult studies conducted in Japan and in India 17‐20 …”
Section: Discussionsupporting
confidence: 76%
“…These results confirm our hypothesis indicating that in general the measurement of 2‐hour OGTT glucose values cannot be replaced by determining FPG, and vice versa. They also support the results of a study conducted in a North Indian population but contrast with those from adult studies conducted in Japan and in India 17‐20 …”
Section: Discussionsupporting
confidence: 76%
“…Fasting plasma glucose increased by 0.011 mmol/L per year, in accord with previous reports [30]. The HOMA-β decreased by 0.85% per year, clearly indicating reduced basal insulin secretion.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have reported the relation of age and gender to postload glycaemia [10,11,13,39–44]. Bando et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bando et al . [11] studied 13 694 Japanese subjects aged between 20 and 83 years and found that age, BMI, SBP and TG influence the 2‐hPG value independently of the FPG. There are some differences between our results and the Japanese study.…”
Section: Discussionmentioning
confidence: 99%